2017
DOI: 10.1038/s41529-017-0019-9
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale investigation of uranium attenuation by arsenic at an abandoned uranium mine, South Terras

Abstract: Detailed mineralogical analysis of soils from the UK's historical uranium mine, South Terras, was performed to elucidate the mechanisms of uranium degradation and migration in the 86 years since abandonment. Soils were sampled from the surface (0-2 cm) and near-surface (25 cm) in two distinct areas of ore processing activities. Bulk soil analysis revealed the presence of high concentrations of uranium (<1690 p.p.m.), arsenic (1830 p.p.m.) and beryllium (~250 p.p.m.), suggesting pedogenic weathering of the coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 21 publications
2
29
0
Order By: Relevance
“…It has been observed that U minerals at South Terras are Cu-phosphate and Cu-arsenate rich, such as metatorbernite and metazeunerite, and were present at depths of ~25 cm (Corkhill et al, 2017;Foulkes et al, 2017;Purvis et al, 2004), consistent with the rhizosphere soils analysed here. In addition to a close association between U, Cu and P in these soils, Cu and P showed similar chemical behaviour to U as determined by sequential extraction analysis (Corkhill et al, 2017). Therefore plant roots and/or mycorrhizal hyphae accessing essential Cu and PO 4 3nutrients from the soil might coincidentally bioaccumulate 238 U.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…It has been observed that U minerals at South Terras are Cu-phosphate and Cu-arsenate rich, such as metatorbernite and metazeunerite, and were present at depths of ~25 cm (Corkhill et al, 2017;Foulkes et al, 2017;Purvis et al, 2004), consistent with the rhizosphere soils analysed here. In addition to a close association between U, Cu and P in these soils, Cu and P showed similar chemical behaviour to U as determined by sequential extraction analysis (Corkhill et al, 2017). Therefore plant roots and/or mycorrhizal hyphae accessing essential Cu and PO 4 3nutrients from the soil might coincidentally bioaccumulate 238 U.…”
Section: Discussionsupporting
confidence: 86%
“…South Terras and Needle's Eye are two ideal field locations for the characterisation of radionuclide transfer from soil into the understory vegetation of temperate woodland. While there has previously been substantial radiochemistry research at Needle's Eye and, to a lesser extent, South Terras (Basham et al, 1991;Corkhill et al, 2017;Foulkes et al, 2017;MacKenzie et al, 1991;Siddeeg et al, 2015), no previous study has investigated the radioecology of these sites. Both locations have soils with 238 U concentrations that greatly exceed the global average (UNSCEAR, 2000) and were similar to or exceeded values determined by a number of radioecology surveys (Blanco Rodriguez et al, 2010;Vera Tomé et al, 2003;Vera Tomé et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 Linear regression of the U L III edge energy position (defined as the energy where the edge step is equal to 0.5) with respect to standards of known oxidation state (UO 2 , Yb 0.5 U 0.5 Ti 2 O 6 and CaUO 4 ) confirmed the uranium oxidation state within the sample. 41…”
Section: Characterisationmentioning
confidence: 99%
“…This causes additional hazards associated with the release of As into water aquifers. [18][19][20][21][22][23][24] In cases when reduction conditions prevail, such as at the Ruprechtov site in the Czech Republic, As occurs in the form of arsenopyrite (FeAsS) in tertiary sediments forming layered aggregates with secondary uraninite and arsenopyrite. 19 Mixed copper uranyl arsenate-phosphate species have been identied in the soils from an abandoned U mine in the UK as a result of many years of the mining activities at the site.…”
Section: Introductionmentioning
confidence: 99%